Tilfangetagelsen af Valdemar II Sejr i Dunstableårbogen - Kjær, Lars (Historisk Tidsskrift, 2014)
The Capture of Valdemar II of Denmark according to the Dunstable Chronicle The capture of King Valdemar 2 and his son in 1223 by count Henrik of Schwerin was a significant event in Danish medieval history. The release of the king was secured only several years later, after paying a hefty ransom, and Valdemar did not subsequently succeed in reestablishing his formerly powerful position in Northern Germany. Among the few and brief sources to the episode is the hitherto overlooked AD 1225 entry in the Dunstable Chronicle. The text of the otherwise reliable chronicle is on this particular matter crammed with factual error and adds little to our knowledge on the event itself. Nevertheless, the brief tale, which is translated into Danish in an appendix to the article, demonstrates certain ideological and literary motifs typical for the epoch such as the tragi-comical nature of drunkenness, and treason through apparent friendship. Allegedly, schemes and circumstances of this kind led to the success of the abduction. Finally, parallelisms and possible connections between the chronicle and other sources are discussed.